Project Activity as a Tool for the Development of Territorial Communities - POLYANSKA , Alla; ZAPUKHLYAK , Ivanna (University Scientific Notes, 2021)
The article substantiates the need to find modern mechanisms for resolving the conflicts between private and public interests, individual and managerial approaches, public and state vision on solving the problems of local community development. It is proved that one of the elements of such a mechanism is the project activity of the united territorial communities, which due to purposefulness, focusing on timeliness and quality of project results, as well as opportunities to attract financial resources from various sources, will increase the efficiency and effectiveness of the united territorial community activity, improvement the quality of public life and strengthening its competitive potential. The project activities of the united territorial communities of Ivano-Frankivsk region were diagnosed, which allowed to establish that short-term and low-budget projects predominate among local communities’ projects, which insufficiently resolve the systemic problems of territorial development due to financial insolvency of existing territorial communities. The directions of further development of the united territorial communities on the basis of project management are outlined.